2014
DOI: 10.1002/phy2.262
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory effects of siRNA-induced myostatin inhibition and exercise on skeletal muscle homeostasis and body composition

Abstract: Inhibition of myostatin (Mstn) stimulates skeletal muscle growth, reduces body fat, and induces a number of metabolic changes. However, it remains unexplored how exercise training modulates the response to Mstn inhibition. The aim of this study was to investigate how siRNA‐mediated Mstn inhibition alone but also in combination with physical activity affects body composition and skeletal muscle homeostasis. Adult mice were treated with Mstn‐targeting siRNA and subjected to a treadmill‐based exercise protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The significantly higher magnitudes were observed in MSTN - ACVR2B (38.4 ± 2.9%) and MSTN - ACVR2A (33.9 ± 1.9%) knock down birds for breast muscle and MSTN (27.1 ± 3.1%) and ACVR2B (27.0 ± 0.5%) knock down birds for leg muscle over control group of birds (27.6 ± 2.1 and 19.3 ± 1.3%, respectively). The similar trend of muscular hypertrophy was observed in MSTN knock down in Zebra fish 37 , catfish 38 and human 39 revealing importance gene silencing for MSTN for enhancing growth.…”
Section: Discussionsupporting
confidence: 68%
“…The significantly higher magnitudes were observed in MSTN - ACVR2B (38.4 ± 2.9%) and MSTN - ACVR2A (33.9 ± 1.9%) knock down birds for breast muscle and MSTN (27.1 ± 3.1%) and ACVR2B (27.0 ± 0.5%) knock down birds for leg muscle over control group of birds (27.6 ± 2.1 and 19.3 ± 1.3%, respectively). The similar trend of muscular hypertrophy was observed in MSTN knock down in Zebra fish 37 , catfish 38 and human 39 revealing importance gene silencing for MSTN for enhancing growth.…”
Section: Discussionsupporting
confidence: 68%
“…The absence of both insulin and IGF-I in the cultural media should be a reason of the unaffected mTOR/p70S6K in follostatin treatment. Therefore, the role of myostatin and follistatin in glucocorticoid-induced muscle development and growth remains to be elucidated with gene interfering technique in future [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of chronic DOX treatment on body composition in mice had not been published at the start of the study (2013); however, in 2017 Wang et al [69] reported decreased fat mass accumulation with ten weeks of DOX treatment in male db/db mice. A major benefit of MSTN reduction therapy is improved body composition, as increased lean mass and decreased fat mass has been reported in constitutive knock-out mice [70,71], while post-developmental models indicate that MSTN reduction prevents fat mass accumulation but does not reduce existing fat mass levels [24,72,73]. DOX treatment, therefore, is potentially a major confounding factor when body composition changes are primary endpoints of a study.…”
Section: Limitationsmentioning
confidence: 99%